Economic Dispatch of Micro-grid Considering Electric Vehicles - Sheng S.W.; Yee Y.S.; Raymond W.J.K.; Mei K.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost reduction; Electric discharges; Electric energy storage; Electric power transmission networks; Electric vehicles; Heuristic algorithms; Linear programming; Operating costs; Scheduling; Solar power generation; Vehicle-to-grid; Decentralised; Deep penetration; Economic Dispatch; Linear-programming; Microgrid; Microgrid systems; Power grids; Renewable energies; Storage systems; Vehicle to grids; Electric load dispatching